Effects of grape seedlings intercropping with post-grafting generation of Impatiens balsamina on different fractions of cadmium content in soil. Issue 4 (February 2019) - Zhong, Lisha; Liu, Na; Xia, Dan; Lin, Lijin; Liao, Ming'an
Abstract: To study the effects of grape seedlings intercropping with post-grafting generation of Impatiens balsamina on different fractions of cadmium (Cd) in soil, a pot experiment was conducted. The results showed that grape seedlings intercropping with post-grafting generations of I. balsamina significantly increased the content of exchangeable Cd in soil. Grape seedlings intercropping with the post-grafting generation of self-rooted grafting by two different sizes seedlings of I. balsamina significantly increased the content of residual Cd (52%), and increased the exchangeable Cd content (19%). In conclusion, grape seedlings were not suitable for intercropping with post-grafting generations of I. balsamina, although some intercropping treatments increased the content of residual Cd.